When the fed speaks: Arguments, emotions, and the microfoundations of Institutions - Harmon, Derek J. (Administrative Science Quarterly)
This study investigates what happens when a prominent leader explicitly reaffirms the taken-for-granted assumptions underlying an institution. While such efforts are usually made to reinforce the institution, I theorize that they actually destabilize the institution and create collective uncertainty by reopening the very considerations that people take for granted. Using speeches made by the chair of the United States Federal Reserve from 1998 to 2014, I demonstrate that reaffirming the taken-for-granted assumptions underlying the monetary policy framework creates uncertainty in the broader financial market. This market reaction is also influenced by emotions present at the time of the speech that shape how the event is interpreted. Speeches conveyed in an overall more positive tone suppress this reaction, while more fear in the business media amplifies it. Moreover, supplementary analyses conducted on speeches during the financial crisis suggest that when the taken-for-grantedness of these assumptions has weakened, reaffirming them no longer creates uncertainty to the same extent. This study expands our understanding of the consequences of communication in market contexts, raises important questions about the trade-offs between public transparency and market stability, and contributes new insights to research on the cognitive and emotional microfoundations of institutions. - Reproduced.